Reconciling East-African Wetland Conservation with Human Needs: Managing Uncertainties in Environmental Policy Design - Matthias Langensiepen; Erick Omwandho Opiyo; Alice A. Kaudia; Denis Rugege; Kyambadde Richard; Erick Akotsi; Dan Ashitiva; Julius K. Ningu; Faustin Munyazikwiye; Theogene Ngaboyamahina; Justin K. Urassa; Michael Ugen; et al. (Wetlands, 2023)
Rapidly developing societies in East-Africa impose increasing pressures on wetlands due to rising food demand and degradation of upland soils. Reconciling wetland conservation with human needs for food and energy is therefore becoming an increasing contentious issue. Stakeholders and actor coalitions generate and apply a great variety of meanings, values, and interests when interacting with wetlands which are hardly predictable. Wetland policy-making is hence fraught with uncertainties which need to be managed for finding solutions to this problem. Based on experiences of a collaborative wetland research in East-Africa we developed a new wetland policy process framework which promotes social deliberation and reconciliation of plural wetland values to reduce these uncertainties. A new cognitive-driven information design (CDID) method has been developed to assist wetland policy-analysts in achieving these aims and also to overcome limitations of prescriptive decision-making. The method employs information and communication technologies to analyze, integrate and visualize complex socio-ecological wetland information for developing policy scenarios. It is applied at all stages of the wetland policy process including agenda setting, identification of plural wetland values, establishment of decision-scenarios, social deliberation during policy formulation, governmental decision-taking, policy implementation and evaluation. A three-stage implementation process is recommended.